2014
DOI: 10.1530/eje-13-1003
|View full text |Cite
|
Sign up to set email alerts
|

TSH measurement is not an appropriate screening test for autonomous functioning thyroid nodules: a retrospective study of 368 patients

Abstract: Objective: Based on the assumption that normal TSH concentration rules out the presence of autonomous functioning thyroid nodules (AFTNs), clinical guidelines on the management of thyroid nodules only recommend a thyroid scan if TSH concentration is subnormal. However, the proportion of AFTN presenting with a normal TSH is unknown. Our objective is therefore to determine the proportion of AFTNs with a normal TSH level to ascertain whether a normal TSH really rules out an AFTN. Design: Retrospective study on 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 23 publications
3
36
0
4
Order By: Relevance
“…Accordingly, comparative studies proved substantial equivalence of 99m Tc-pertechnetate and radioiodine in clinical practice [1,2,36,37]. Third, criteria adopted to exclude from TS patients with potential interferences on thyroid function were detailed in three of selected papers [23,25,27]. Anyway, even if such criteria were not stated in remaining papers, scrutiny for interferences is a standard of care in nuclear medicine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, comparative studies proved substantial equivalence of 99m Tc-pertechnetate and radioiodine in clinical practice [1,2,36,37]. Third, criteria adopted to exclude from TS patients with potential interferences on thyroid function were detailed in three of selected papers [23,25,27]. Anyway, even if such criteria were not stated in remaining papers, scrutiny for interferences is a standard of care in nuclear medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The full text of six eligible articles was retrieved and two additional studies were found screening the references of the selected articles. Finally, eight articles including series of patients with AFTN were selected for the meta-analysis [16,[21][22][23][24][25][26][27] (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the EANM believes that thyroid scintigraphy still has its place in the diagnostic workup of nodular thyroid disease, especially in regions, including a number of EANM member countries, with a known or recently alleviated iodine deficiency. In such populations a normal TSH level cannot rule out thyroid autonomy [8][9][10][11]. In their retrospective study, Chami et al [9] found that 49 % of patients with an autonomously functioning focal thyroid nodule had a normal TSH level.…”
mentioning
confidence: 99%